2009
DOI: 10.1111/j.1365-2745.2009.01600.x
|View full text |Cite
|
Sign up to set email alerts
|

Do linear landscape elements in farmland act as biological corridors for pollen dispersal?

Abstract: Summary1. Habitat fragmentation in agricultural landscapes has reduced the population sizes of many plant species while increasing their spatial isolation. Restoration or maintenance of the connectivity by gene flow between the fragmented patches may be determinant to sustaining viable populations, especially for insect-pollinated species. Functional biological corridors facilitating pollen flow between remnants in a human-dominated matrix might achieve this. 2. Dye dispersal was investigated for the extremely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 90 publications
5
97
0
2
Order By: Relevance
“…Moreover, ditch networks are one of the most frequent non-cropped networks in cultivated landscapes, thereby providing a key service of ecological corridors (Herzon and Helenius 2008). These corridors permit the movement of amphibians, mammals, or insects that would otherwise be restricted in hostile and intensively cropped areas (Herzon and Helenius 2008;Van Geert et al 2010). Ditch networks may also connect fractionated populations and favor Ditches and especially vegetated ditches hold inherent pesticide retention power.…”
Section: Biodiversity Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ditch networks are one of the most frequent non-cropped networks in cultivated landscapes, thereby providing a key service of ecological corridors (Herzon and Helenius 2008). These corridors permit the movement of amphibians, mammals, or insects that would otherwise be restricted in hostile and intensively cropped areas (Herzon and Helenius 2008;Van Geert et al 2010). Ditch networks may also connect fractionated populations and favor Ditches and especially vegetated ditches hold inherent pesticide retention power.…”
Section: Biodiversity Conservationmentioning
confidence: 99%
“…The reduction of the more hydrophobic pesticide loads is generally higher than for the less hydrophobic ones, but this is conditioned by ditch characteristics nd missing data, OC organic carbon their survival and renewal. Indeed, habitat fractionation leads to plant and animal population isolation and threatens plant and animal long-term survival, especially for seed-setting plant species, which require insects for pollination (Van Geert et al 2010). Van Geert and collaborators (2010) found that pollen dispersal was greater when plant populations were connected by ditches.…”
Section: Biodiversity Conservationmentioning
confidence: 99%
“…Although quarry operations represent a dramatic land degradation; shortly after their abandonment spontaneous succession turns them into diverse habitat mosaics supporting a rich butterfly fauna (NovĂĄk and Konvička 2006;Tropek et al 2010Tropek et al , Č ermĂĄkovĂĄ et al 2010. A similar situation can be observed in other artificial environments especially those created by infrastructure development, such as road margins, railway embankments, gravel pits, or ruderal habitats in suburbia (Van Geert et al 2010;Lenda et al 2012;Moron et al 2014;Nowicki et al 2013). Nevertheless, it must be underlined that such man-made environments offer favourable conditions only in their early successional stages, hence only in the short-term, and later on they require management just like natural habitats in order to prevent overgrowing.…”
Section: Discussionmentioning
confidence: 66%
“…For example, for highly mobile species, the restoration processes can consider creating a 'stepping stone' habitat (e.g., Ottewell et al 2009), whereas dispersal limited species may need more contiguous linear corridors of high-quality habitat (Tewksbury et al 2002) to facilitate movement through inhospitable matrices. In fact, within agricultural settings, plant populations connected by corridors (Townsend and Levey 2005;Van Geert et al 2010) or highly biodiverse matrices (Jha and Dick 2010) have been shown to participate in extensive pollen transfer. Thus, habitat restoration that facilitates pollinator movement has the potential to support improved pollination services across natural and human-altered landscapes, particularly in light of current and plausible future changes in local and regional weather patterns and climate.…”
Section: Regional Habitat Restorationmentioning
confidence: 99%